Recent Invasion of the Endemic Banggai Cardinalfish, Pterapogon kauderni at The Strait of Bali: Assessment of the Habitat Type and Population Structure - I Nyoman Giri Putra; I Dewa Nyoman Nurweda Putra (Marine Science Department Diponegoro University, 2019)
The demands of marine organisms for the aquarium trade are remain high and seems continue to increase. Consequently, many of marine organisms has been spread out from its natural habitat as in the case of endemic Banggai cardinalfish, (Pterapogon kauderni). That has invaded “new” habitat since it being trade in 1995. In recent years, a small populations of P. kauderni is known to be exist in a narrow bay near the Gilimanuk harbor, Bali. An underwater visual fish census survey was conducted on June 2018 to estimate the habitat types and densities of P. kauderni. Additionally, 23 specimens of P. kauderni were collected randomly in order to assess biological parameters such as the length-weight relationship. We successfully recorded 30 groups of P. kauderni that inhabit a shallow areas with a depth range between 0.5m to 2m. Of these, more than 90% of the groups were found to be associated with sea urchin (Diadema sp.) while the rest were found to live together with branching coral (Acropora sp.) and branching sponge (Ptylocaulis sp.). Total number of fish observed during the survey were 381 individuals. The fish density is 0.76 individu.m-2. Length-weight relationship showed that P. kauderni exhibit is negative allometry (b<3) which mean that the increase in length is faster than the weight gain. Interestingly, from the 23 specimens collected, none of these were sexually mature (SL<41 mm) which may indicated that the population of P. kauderni in Bali are under serious threats of exploitation.